2022
DOI: 10.1149/1945-7111/ac68a4
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Biosensor for Detection of Cichoric Acid as an Anti-Alzheimer’s Disease Agent in Chicory Samples Based on Setaria-Like Trimetallic Nanodendrites Decorated NH2-RGO Flakes

Abstract: Chicoric acid (CA), a phenolic acid from chicory, is regarded as a powerful ingredient against oxidative stress and obesity. It's believed to be a promising drug candidate as its healing features prevent memory loss. However, existent methods for CA detection limit its practical applications in purification and further pharmacological study due to lack of accuracy. Therefore, it is crucial to find a forceful approach to precisely analyze cichoric acid for anti-AD research. In this work, we reported a facile m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
1
0
0
Order By: Relevance
“…In contrast, in the present study the rats in G, C, and G+C groups showed a protective impact against the neurobehavioral disterbance of ALCL3 when administered prior to ALCL3. These findings consistent with many studies that concluded the powerful antioxidant abilities of Ginko biloba and Cicuriun Intybus each one alone (Rojas et al, 2016; Liu and Guo, 2020; Li et al, 2022) [35,25,23] . The use of all these herbs were conducive to the reduction of inflammatory processes within the nervous system (Hirata et al, 2019) [16] .…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, in the present study the rats in G, C, and G+C groups showed a protective impact against the neurobehavioral disterbance of ALCL3 when administered prior to ALCL3. These findings consistent with many studies that concluded the powerful antioxidant abilities of Ginko biloba and Cicuriun Intybus each one alone (Rojas et al, 2016; Liu and Guo, 2020; Li et al, 2022) [35,25,23] . The use of all these herbs were conducive to the reduction of inflammatory processes within the nervous system (Hirata et al, 2019) [16] .…”
Section: Discussionsupporting
confidence: 90%